METHODOLOGICAL FOUNDATIONS OF DEVELOPING STUDENTS’ MUSICAL EDUCATION IN GENERAL SECONDARY SCHOOLS - Adkhamjonova Mubina Nosirjon qizi (Modern American Journals, 2025)
The methodological foundations of developing students’ musical education are not only aimed at enriching music lessons in terms of content but also serve as a core direction in fostering musical culture, aesthetic taste, and creativity among students. Appropriately chosen approaches and methods can effectively develop each student’s musical thinking, emotional perception, and expressive skills.
Keywords: Musical education, methodology, listening, performance, rhythmics, methods, creativity, multimedia tools, creative activity.